(untitled) (Research, Society and Development, 2021)
Objective: To identify the social and spatial inequalities of abortion deaths in Brazil, and simultaneously assess the evolution of these data over the past few years. Methods: Secondary data on deaths from abortions, registered in the SIM/SUS, from 2000 to 2020, will be used to analyze the coefficients of mortality from abortion in Brazil. These coefficients will be calculated according to variables related to the sociodemographic profile of women in the SIM/SUS database, which constitute the variables of interest in this study. Results: After surveying data, it was possible to notice that the frequency among women who most die from abortion in Brazil are women of childbearing age 20-29 years old, single, and brown. Final Considerations: Evidence was found that proves the large number of women of childbearing age and with a low level of education, emphasizing the importance of implementing sexual education measures and strengthening family planning, in order to avoid episodes of abortion and unwanted pregnancies.